Indian life and health insurance industry a marketing approach - Dewan, Novi. (International Management Science)
Due to its massive population, sound economic fundamentals, dynamic improvements in the insurance regulatory framework and an increasing awareness amongst Indians about the relevance of insurances, India offers extensive opportunities for market entry and expansion in the insurance industry. "The book reveals insightful ideas about the Indian insurance industry along with a discussion on the best practices of the marketing mix. Novi's impressive thesis, which forms the basis of this book, prompted me to contribute to her research with an India perspective. I am sure that this book will be an important reference material for emerging markets with similar growth dynamics." Trevor Bull, Managing Director Tata AIG Life Insurance Company Ltd. “The analysis presented stands out by being based on a thorough understanding of India and the life and health insurance industry investigated.” Professor Dr. Martin Fassnacht Associate Dean and Endowed Chair of Marketing WHU – Otto Beisheim School of Management “Only very few insurance companies really follow a strong market-driven approach. I consider this book a must-read for insurance executives, not only for those who are interested in the Indian market but for all of those who want to instil more market-orientation into their organisations.” Dr. Dirk Schmidt-Gallas Partner and Global Head of Insurance Simon-Kucher & Partners. Insurance industry in India -- Life insurance -- Health insurance -- Conclusion.